The relationship between childbirth self-efficacy and coping styles of problem based and emotive based in nulliparous pregnant women - Mahsima Banaei Heravan; Sadaf Rashki (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Vaginal childbirth is the most stressful physical and mental event for most women, which necessitates the use of coping styles. Furthermore, childbirth self-efficacy will be one of the effective factors to cope with this stressful situation and doing compatible behaviors with childbirth pain. Therefore, the aim of this study was to determine the relationship between childbirth self-efficacy and coping styles of problem based and emotive based in nulliparous pregnant women. MATERIALS AND METHODS: This study is a descriptive-correlational study that is done over 323 nulliparous pregnant women attending the health centers in the city of Zahedan in 2020-2021. Data were collected by participants' demographic questionnaire, childbirth self-efficacy questionnaire of Lowe, and coping styles questionnaire of Folkman and Lazarus. The data were analyzed using Spearman's correlation coefficient test, linear regressions model, and multiple regression in SPSS software version 22. P < 0.05 was considered statistically significant. RESULTS: Results of Spearman's correlation coefficient test showed a significant direct correlation between problem-based coping style and childbirth self-efficacy (P = 0/017, r = 0.13); but, there was no significant direct correlation with emotive-based coping style (P = 0/782, r = 0.01). According to the linear regressions model, just the problem-based coping style is predicted childbirth self-efficacy (P = 0/006). CONCLUSIONS: According to the findings, nulliparous pregnant women should be responsible, have a positive reassessment of vaginal childbirth, plan to solve their problems, and look for social support (all of these are part of a problem-based coping style) to increase and improve their childbirth self-efficacy. Furthermore, designing appropriate educational interventions based on problem-based coping style is necessary.